2018
DOI: 10.1590/2317-1545v40n2191893
|View full text |Cite
|
Sign up to set email alerts
|

Late seed maturation improves the preservation of seedling emergence during storage in soybean

Abstract: -Long-term survival during dry storage or longevity is a pre-requisite to avoid deterioration, leading to loss of vigor. Longevity is routinely evaluated by the ability to germinate after storage. It increases progressively during seed maturation, after the acquisition of desiccation tolerance. However, the capacity to germinate represents only a part of the success of crop establishment. How seed maturation affects the resistance of several traits, as vigor, associated with seedling establishment, against det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…He also noted that, because data are often not collected to calculate physiological maturity accurately, indirect (visual) indicators are often applied – such as the appearance of a black layer in maize ( Zea mays L.) seeds (Egli, 1998). Mass maturity Given that the definition of physiological maturity had become compromised and so misleading in seed science, the term mass maturity was proposed to designate the end of the seed-filling phase (Ellis and Pieta Filho, 1992). For the avoidance of doubt, mass maturity is the seed developmental stage that Shaw and Loomis (1950) termed physiological maturity. Maturation drying The moisture content of seeds declines throughout their development and maturation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…He also noted that, because data are often not collected to calculate physiological maturity accurately, indirect (visual) indicators are often applied – such as the appearance of a black layer in maize ( Zea mays L.) seeds (Egli, 1998). Mass maturity Given that the definition of physiological maturity had become compromised and so misleading in seed science, the term mass maturity was proposed to designate the end of the seed-filling phase (Ellis and Pieta Filho, 1992). For the avoidance of doubt, mass maturity is the seed developmental stage that Shaw and Loomis (1950) termed physiological maturity. Maturation drying The moisture content of seeds declines throughout their development and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the definition of physiological maturity had become compromised and so misleading in seed science, the term mass maturity was proposed to designate the end of the seed-filling phase (Ellis and Pieta Filho, 1992). For the avoidance of doubt, mass maturity is the seed developmental stage that Shaw and Loomis (1950) termed physiological maturity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed longevity continues to increase after the seeds have acquired desiccation tolerance, in the late maturation phase of seed development [64][65][66][67]. However, the time when 'final' or 'maximum achievable' longevity is reached and how long it is maintained thereafter will vary between species, varieties, accessions, and seasons.…”
Section: Maturity At Harvestmentioning
confidence: 99%
“…However, we still know little about the attributes involved in the acquisition of the physiological quality of peanut seeds and when they are acquired. One strategy to fill this gap is to study the acquisition of quality in peanut seeds during maturation, which has been reported for legumes such as soybean [9,10], Medicago truncatula [11,12] and cowpea beans [13].…”
Section: Introductionmentioning
confidence: 99%